Teacher Candidates as the Teacher of Record Assists Partner School Districts With the Teacher Shortage - Rich, Gregory; Gray Smith, Linda; Alexander, Kristi (Educational (Re)naissance, 2020)
This research essay examined a growing trend in a rural area of the Midwest where PK–12 school districts are partnering with a local university to hire teacher candidates (TCs) as the Teachers of Record (TORs). Many rural school districts are challenged to address the teacher shortage. As a result, many school districts are hiring TCs as the TOR during the TC’s student-teaching experience. Due to the limited research on the topic, this paper aimed to determine if appointing the TC as the TOR was an effective practice. We used three data sources to gauge the perceptions of the TC, the TC’s mentor, and the TC’s administrator. Meeting the needs of partnering districts and providing quality placements for TCs engaged in the culminating field experience can be mutually beneficial for teacher candidates, the school district, and the university.